Realizing an innovative design vision for clothes suitable for girls with visual impairments - Qadi, Roua Suhail Hassan (Journal of Humanities & Social Sciences, 2023)
This study aimed to identify the essential characteristics of clothing suitable for girls with visual impairments, assess their clothing needs, and present appropriate design proposals that provide comfort, ease of choice, and use. The researcher used a descriptive and analytical approach to study clothing needs and an experimental approach to present design proposals. The study concluded that girls with visual impairments rely on their sense of touch to recognize their clothes and prefer soft, comfortable materials, front openings, and one-piece clothes that do not require coordination. Education, age, and economic status also play a crucial role in using technological aids for blind people. The proposed designs were evaluated, and the first design was the best in achieving the functional aspect, providing protection for the body, quick and easy put-on and take-off, easy identification of clothes through texture, design, drawings, or needle, and ease of care. The third design was the best in achieving the aesthetic aspect, with harmony between parts, compatibility between colors and materials, and conformity with prevailing fashion. This study recommends the importance of allocating training programs to teach clothing practices and care for visually impaired girls.